Energy savings and increased electric vehicle range through improved battery thermal management. (25th May 2016) - Smith, Joshua; Hinterberger, Michael; Schneider, Christoph; Koehler, Juergen
Abstract: Lithium-ion cells are temperature sensitive: operation outside the optimal operating range causes premature aging and correspondingly reduces vehicle range and battery system lifetime. In order to meet consumer demands for electric and hybrid-electric vehicle performance, especially in adverse climates, a battery thermal management system (BTMS) is often required. This work presents a novel experimental method for analyzing BTMS using three sample cooling plate concepts. For each concept, the input parameters (ambient temperature, coolant temperature and coolant flow rate) are varied and the resulting effect on the average temperature and temperature distribution across and between cells is compared. Additionally, the pressure loss along the coolant path is utilized as an indicator of energy efficiency. Using the presented methodology, various cooling plate layouts optimized for production alternative techniques are compared to the state of the art. It is shown that these production-optimized cooling plates provide sufficient thermal performance with the additional benefit of mechanical integration within the battery and/or vehicle system. It is also shown that the coolant flow influences battery cell thermal behavior more than the solid material and that pressure drop is more sensitive to geometrical changes in the cooling plate than temperature changes at the module.